Organizational video-ethnography revisited making visible material, embodied and sensory practices - Palgrave Macmillan; Palgrave Macmillan; Grosjean, Sylvie; Matte, Frederik (Cham Palgrave Macmillan, 2022)
This book explores the undeveloped potential of video-ethnography to study the material, embodied and sensory dimensions of workplace practices. With the growing interest in sociomateriality and the development of research on the embodied and sensory dimensions of organizational practices, some methodological challenges of this type of research need to be addressed. The main purpose of this book is to present various forms of video-ethnography that make organizational phenomena visible and help better appreciate the organizing properties of bodies, affects, senses and spaces in workplace practices. To do so, illustrative cases based on video-ethnography was discussed to understand how experiential and unspoken ways of knowing produced through a video-based approach can be made meaningful and relevant to study the material, embodied and sensory dimension of work practices. This book is addressed to researchers and students in social sciences and organizational studies and offers a methodological reflection on how to study the material, embodied, and sensory dimensions of organizational life. Sylvie Grosjean is Professor at University of Ottawa (Canada). Her research focuses on design and use of telehealth innovations. She uses qualitative methods and develops Participatory Design approaches in health care settings. She has published in Symbolic Interaction, Management Communication Quaterly, Journal for Communication Studies, Sciences du Design, Innovations, Knowledge-Based Systems. Frederik Matte is Professor at University of Ottawa (Canada). He studies tensions in the extreme and emergency situations faced by international non-governmental organizations (INGOs). He has published in the International Journal of Communication, Journal of Communication, Communication Monographs, Discourse and Communication and Pragmatics & Society.
Keywords: Organizational behavior .; Organizational sociology -- Research -- Methodology .; Video recording